Konflik di Laut Arktik Ditinjau dari Perspektif Kanada (Sengketa Rabung Lomonosov) - Fajar Sanny Mutmainnah (UIR Press, 2021)
The melting of ice in the Arctic Ocean which is faster than researchers think is a result of global warming. The impact of this incident is in the form of positive and negative things, but what has emerged to the surface of the international world is its negative side from the dimensions of international politics. This has triggered tensions between countries around the Arctic Sea area, because each country is trying to prove its claim to the melting sea's territories. This conflict attacked the 4 main pillars of The Northern Strategy of Canada program made by the Government of Canada which made Canada do several things to follow up. The researcher used a Neorealism approach with a descriptive - analytic approach to explain the problem. Efforts to deal with it are carried out with the concept of negotiation through UNCLOS, as well as various methods and mechanisms aimed at finding a bright spot among warring countries, in this discussion from the Canadian perspective. Countries in the region must also work together, especially in avoiding the use of military force as an effort to protect the environmental ecosystem, including indigenous peoples from disputing countries who have a role in the decision making of each country. This research was made to map the conflict that occurred as well as to provide a number of solutions to this case.